2013
DOI: 10.4161/epi.25178
|View full text |Cite
|
Sign up to set email alerts
|

Association between hypermethylation of DNA repetitive elements in white blood cell DNA and early-onset colorectal cancer

Abstract: Changes in the methylation levels of DNA from white blood cells (WBCs) are putatively associated with an elevated risk for several cancers. The aim of this study was to investigate the association between colorectal cancer (CRC) and the methylation status of three DNA repetitive elements in DNA from peripheral blood. WBC DNA from 539 CRC cases diagnosed before 60 years of age and 242 sex and age frequency-matched healthy controls from the Australasian Colorectal Cancer Family Registry were assessed for methyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 49 publications
2
33
0
Order By: Relevance
“…Compared with normal controls, L1 hypermethylation was observed in white blood cells of pancreatic, 49 epithelial ovarian, 50 and colorectal 51 cancer patients. As for melanoma 52 and HCC, 53 serum L1s were hypomethylated relative to normal controls.…”
mentioning
confidence: 99%
“…Compared with normal controls, L1 hypermethylation was observed in white blood cells of pancreatic, 49 epithelial ovarian, 50 and colorectal 51 cancer patients. As for melanoma 52 and HCC, 53 serum L1s were hypomethylated relative to normal controls.…”
mentioning
confidence: 99%
“…However, because of nonspecific symptoms in the early stage and lack of effective diagnostic biomarkers, a low early diagnostic rate brings challenges for effective treatment. Abnormal methylation biomarkers have proven to be useful in diagnosing numerous cancers [102,103]. In the current study, the results demonstrated that the combined sensitivity, specificity, and AUC values of CDKN2A methylation were 0.36, 0.96, and 0.77, respectively, indicating that detection of CDKN2A promoter methylation has a moderate diagnostic accuracy for HNSCC.…”
Section: Discussionmentioning
confidence: 61%
“…In this study, we investigated EPHX1 methylation in the peripheral blood DNA and tested the association between CBZ-metabolites concentration. Methylation levels in peripheral blood DNA have been widely investigated in various diseases, including diabetes [23], obesity [24], major depression [25], and various cancers [26][27][28]. Here we provided its strong association with lower CBZ-metabolites concentration in CBZ-resistant group.…”
Section: Discussionmentioning
confidence: 67%